2001
DOI: 10.1111/j.1600-051x.2001.280109.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of margins of restorations on the periodontal tissues over 26 years

Abstract: Aim: The purpose of this investigation was to examine the long‐term relationship between dental restorations and periodontal health. Material and Methods: The data derived from a 26‐year longitudinal study of a group of Scandinavian middle‐class males characterized by good to moderate oral hygiene and regular dental check‐ups. At each of 7 examinations between 1969 and 1995, the mesial and buccal surfaces were scored for dental, restorative and periodontal parameters. The mesial sites of premolars and molars o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 23 publications
3
62
1
8
Order By: Relevance
“…Class V and Class II restorative margins may be subgingival, which could make cleaning difficult and provide areas and pockets for bacterial growth. It is generally accepted that overhanging restorations promote gingivitis by promoting the local accumulation of bacterial plaque, and restorations placed below the gingival margin could be detrimental to gingival and periodontal health [55,56,57]. For example, a previous study showed that over a one-year observation period of subgingival restorations, the composite group had a significant increase in the total bacterial counts, hence composite restorations may have some negative effects on the quantity and quality of subgingival plaque [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Class V and Class II restorative margins may be subgingival, which could make cleaning difficult and provide areas and pockets for bacterial growth. It is generally accepted that overhanging restorations promote gingivitis by promoting the local accumulation of bacterial plaque, and restorations placed below the gingival margin could be detrimental to gingival and periodontal health [55,56,57]. For example, a previous study showed that over a one-year observation period of subgingival restorations, the composite group had a significant increase in the total bacterial counts, hence composite restorations may have some negative effects on the quantity and quality of subgingival plaque [56].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous study showed that over a one-year observation period of subgingival restorations, the composite group had a significant increase in the total bacterial counts, hence composite restorations may have some negative effects on the quantity and quality of subgingival plaque [56]. This could, in turn, lead to soft tissue inflammation, gingivitis, and the development of periodontitis in the area [55,56,57]. Therefore, the incorporation of MPC into a Class V or II restoration with gingival or subgingival margins could help repel proteins/bacterial attachment and growth, in order to reduce inflammation, gingivitis, and periodontitis in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Although subgingival restoration margins seem to be detrimental to gingival and periodontal health over a long period of time (Schatzle et al. ), short‐term data from clinical studies could not reveal more pronounced gingival inflammation and plaque accumulation if class V restorations made of different tooth coloured filling materials were covered with coronally advanced pedicle flaps (Lucchesi et al. , Santamaria et al.…”
Section: Tissue Integration and Volume Stabilitymentioning
confidence: 99%
“…There is little doubt that poorly contoured restorations can increase plaque retention and/or violate the biologic width. However, there is controversy about whether the placement of a new restoration pre‐disposes the adjacent periodontal tissues to future breakdown (Albandar et al 1995, Schatzle et al 2001, Paolantonio et al 2004).…”
mentioning
confidence: 99%